Desires and attitudes of outpatients and physicians regarding the use of teleurology during the pandemic: a prospective survey study - Karabulut, Ibrahim; Demirdogen, Saban Oguz; Ramazanoglu, Mehmet Akif; Sam, Emre; Cinislioglu, Ahmet Emre; Al, Salih; Altay, Mehmet Sefa; Yilmazel, Fatih Kursat; Bicaklioglu, Fatih; Aydin, Hasan Riza; Adanur, Senol (Aktuelle Urologie, 2022)
Objective: It is not known to date how many patients admitted to urology outpatient clinics are willing to use telemedicine. We aimed to investigate knowledge levels and attitudes concerning the utilization of teleurology by patients applying to urology outpatient clinics. Methods: This prospective multicentre survey study included 334 patients aged 18–65 years who applied to an urology outpatient clinics. The patients were asked questions about their attitudes and expectations regarding teleurology. Diseases were divided into seven subgroups due to the broad spectrum of diagnoses. Physicians’ and patients’ opinions on whether it was possible to manage the current medical condition via teleurology were recorded. Results: 69.5% of patients stated that they had sufficient technical skills to use teleurology by themselves for medical examination. 55.4% of patients and 78.4% of physicians responded that the existing complaints were suitable for teleurology. Both patients and physicians deemed genital system diseases and urinary tract infections suitable for teleurology (p<0.001, p<0.001 for physicians, and p<0.001, p<0.001 for patients), whereas urine transport, storage and emptying disorders (p=0.003) and benign prostatic hyperplasia (p=0.029) were deemed to be suitable for teleurology only by the physicians. Conclusion: Our study shows that (i) the majority of our patient population has a telecommunications infrastructure suitable for teleurology, (ii) teleurology has aroused interest among patients, particularly during the pandemic period, and (iii) physicians and patients have high expectations that the problem can be solved with teleurology in suitable patients.
Keywords: Teleurologie; Telemedizin; Urologische Praxis; Pandemie